Hydrological properties of cork container media - Carmona, E.; Ordovas, J.; Moreno, M. T.; Aviles, M.; Aguado, M. T.; Ortega, M. C. (HORTSCIENCE, 2003)
Static hydrological properties \{[\}aeration capacity; easily available water, reserve water, water release curves: theta(v)(Psi(m)), and specific humidity curves] and dynamic hydrological properties (saturated and unsaturated hydraulic conductivity) of substrates based on industrial cork residue (the bark of Quercus suber L.) and cork compost were studied. Samples of similar granulometry have been used to establish the effect of cork composting on the aforementioned physical properties. Different models were tested to describe the mechanism of water release from these materials. Van Genuchten's model (Van Genuchten, 1978) was the best fit and produced specific humidity curves that revealed slight differences in the ratio of water capacity function. When cork residues were composted for 7 months, important changes occurred in hydrological properties of the material as it became more wettable. Water retention significantly increased from 45% to 54%, at a potential of 5 kPa, although this did not necessarily result in increased water available to plants. A study of the unsaturated hydraulic conductivity (K-unsat) of these materials revealed a significant decrease in the K-unsat water potential at 0-5 kPa, which corresponds to the range in which the irrigation with these substrates was usually carried out. The long composting process resulted in increased K-unsat between 4 and 5 times that of uncomposted material, which would improve the water supply to the plant.
The following values have no corresponding Zotero field: pub-location: 113 S WEST ST, STE 200, ALEXANDRIA, VA 22314-2851 USA publisher: AMER SOC HORTICULTURAL SCIENCE
Keywords: growing media; horticultural substrate; hydraulic conductivity; physical properties; water release curves

Characteristics of internal porosity of cork container media - Ordovas, J.; Carmona, E.; Moreno, M. T.; Ortega, M. C. (HORTSCIENCE, 1996)
The structure of cork (Quercus suber L.) bark presents a series of characteristics, suggesting that internal porosity is partly occluded. This study determined the porosity in the waste cork industry (C) and when such waste product had been composted during 4 (CC-4), 7 (CC-7), and 10.5 months (CC-10.5). The particle density of the intact and finely ground material differed significantly in all particle size ranges larger than 0.5 mm. The porosity of the cork substrates ranged from 80% to 94% of the total volume, according to granulometry and the degree of decomposition. However, large particles and less decomposed material with a high porosity had up to 10% of the total volume as occluded pores. The material's effective porosity varied slightly between the various particle sizes and degrees of decomposition, which ranged between 80% and 89%, having an average value of 85%. The ash content was highly correlated with the particle density of the finely ground material. Nevertheless, and due to occluded porosity, we cannot estimate the `'effective porosity'' from the ashes; therefore, we must resort to techniques that involve the displacement of a fluid, such as liquids or gas pycnometry or submersion.
The following values have no corresponding Zotero field: pub-location: 701 NORTH SAINT ASAPH STREET, ALEXANDRIA, VA 22314-1998 publisher: AMER SOC HORTICULTURAL SCIENCE
Keywords: ash content; effective porosity; particle density; total porosity